The Effect of Financial Attitude and Financial Knowledge on the Financial Performance of Small and Medium Enterprises (SMEs) with the Application of Management Accounting as a Mediator - Surenggono Surenggono; Siti Djamilah (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2022)
The financial performance of SMEs requires the application of management accounting knowledge in carrying out their activities, while the application of management accounting is influenced by the influence of financial attitudes and financial knowledge. The purpose of this study was to examine the effect of financial attitudes and financial knowledge on financial performance with the application of management accounting as a mediator. The sample of this research is SMEs in Surabaya and Malang with the following criteria: at least they have started a business for 2 years. The sample size is 123 SMEs. The analytical technique used is the structural equation modeling (SEM). Before testing the hypothesis, the validity and reliability tests are first carried out and show valid and reliable results. The results of hypothesis testing indicate that the financial attitude of SMEs has a significant effect on the application of management accounting, financial knowledge of SMEs has a significant effect on the application of management accounting and the application of management accounting has an effect on the performance of SMEs. Therefore, it is hoped that related parties, especially government agencies, need to provide intensive and varied training to SME (small and medium enterprises) on financial attitudes and financial knowledge. In addition to SME trying to develop their potential, especially in the field of financial attitudes and knowledge. This research is limited to a sample of SMEs in the cities of Surabaya and Malang, therefore further research can use a wider research sample with the addition of independent variables of SMEs' financial perceptions.